Design and synthesis of pyromellitic diimide‐based donor–acceptor conjugated polymers for photovoltaic application. (30th June 2014) - Luo, Chunhua; Shen, Zhitao; Meng, Xiangjian; Han, Li; Sun, Shuo; Lin, Tie; Sun, Jinglan; Peng, Hui; Chu, Junhao
<x xml:space="preserve">Abstract</x> Three of conjugated polymers based on pyromellitic diimide (PMDI) as the acceptor unit and thienothiophene (TT) as the donor unit were successfully synthesized by Stille coupling. The effect of the side chain length and thiophene π‐bridge on the polymers' optical and electrochemical properties was investigated. Electrochemical characterization indicated that these polymers have deep highest occupied molecular orbital energy levels between −5.7 and −5.8 eV. Polymer solar cells were fabricated by using these PMDI‐based polymers as the donor and [6, 6]‐phenyl‐C61‐butyric acid methyl ester as the acceptor. The polymer P1 whose PMDI unit was functionalized with 2‐ethylhexyl side chain shows the higher short‐circuit current (Jsc) and fill factor (FF) compared with that of P2 with a 2‐octyldodecyl side chain on the PMDI unit. The results also illustrate that the insertion of a thiophene π‐bridge between PMDI and TT (the polymer P3) leads to the broader absorption and better photovoltaic performance. The best performance was obtained from the cell based on the polymer P3 with a power conversion efficiency of 0.43% under the illumination of AM 1.5 G, 100 mW/cm2. Copyright © 2014 John Wiley & Sons, Ltd.